Role of inflammation in Myocardial Infarction with Non-Obstructive Coronary Arteries. (14th October 2021) - Espinosa Pascual, M J; Lopez Pais, J; Izquierdo Coronel, B; Nieto Ibanez, D; Galan Gil, D; Perela Alvarez, C; Olsen Rodriguez, R; Abad Romero, R; Moreno Vinues, C; Fraile Sanz, A; Awamleh Garcia, P; Mata Caballero, R; et al.
Abstract: Background: The characteristics of patients with Myocardial Infarction with Non-Obstructive Coronary Arteries (MINOCA) differ from those with Myocardial Infarction with Obstructive Coronary Artery Disease (MI-CAD). Thus, the mechanisms involved, such as inflammation, may be different. The objective of this study is to analyze the relationship between pro-inflammatory conditions and MINOCA, as well as the impact on their prognosis. Methods: An analytical and observational study, including all patients admitted to our hospital with myocardial infarction and who underwent coronary angiography in the last four years (2016–2020; n=712). According to the definitions of the 2019 AHA Scientific Statement on Diagnosis and Management of MINOCA and ESC 2020 guidelines on Acute Coronary Syndromes in Patients Presenting without Persistent ST-Segment Elevation, we classified the patients into two groups: MI-CAD (n=643) and MINOCA (n=69). Besides general data, we recorded specific information about pro-inflammatory conditions (prevalence of autoimmune diseases, connective tissue disorders, and active infections and neoplasms). We also assessed C-reactive protein (C-RP) at admission, peak CK-MB and troponin levels. Follow-up analysis included death from any cause, major adverse cardiac events (MACE: cardiac death, MI, stroke), readmissions due to cardiovascular causes, and in-hospital mortality. Results: The composite of pro-inflammatory conditions (autoimmune pathologies, connective tissue diseases and active cancer and infections) was significantly higher in the MINOCA group (30.4% vs 14.6%, p<0.001). Patients with MINOCA had higher rates of connective tissue disorders (5.8% vs 1.4%, p 0.01), and autoimmune diseases (14.5% vs 7.8%, p 0.058) tended to be more frequent in these patients. However, MINOCA patients had lower C-RP levels (180 vs 206mg/L, p<0.001), probably because they have smaller infarcts (peak CK-MB: 228 vs 325 U/L, p<0.001; high-sensitivity cardiac troponin T levels: 111 vs 176ng/L, p<0.001). In the follow-up of MINOCA patients, MACE did not occur more frequently in those patients with inflammatory conditions (4.8% vs 13%, p 0.3) than those without them. Moreover, pro-inflammatory disorders were not related to significantly higher mortality from any cause (8.7% vs 10%, p 0.86) nor readmissions due to cardiovascular causes (19.6% vs 23.8%, p 0.6). Our median follow-up was 29 months. There were no differences in in-hospital mortality. Conclusion: This study suggests that pro-inflammatory disorders may be a risk factor for developing MINOCA without resulting in an unfavourable short- and long-term prognosis. Further research is needed to confirm this finding and identify its optimal management. FUNDunding Acknowledgement: Type of funding sources: None.